Segmentation Of Kartu Halo Customers Based On Lifestyle In Telkomsel Branch Manado - Wijaya, Wandi; Hasbi, Imanuddin (BIMA Journal (Business, Management, & Accounting Journal), 2022)
The sales of Kartu Halo products in Branch Manado every month at 2018 have increased significantly, this is indicated by the average increased in customer base from early January to August in 2018 of 982 customers. The increase of customer base also inline with the economic growth of North Sulawesi by 6.49% Year on Year in 2018. With the increase in economic growth, the level of expenditure in the city of Manado also increases every month, spending in the non-food sector reaches 50.76% of total monthly expenditure. 30.26% are in the goods and services sector. In large and developing cities in Indonesia has the potential for growth and lifestyle changes in terms of telecommunications services needs. Shifting of consumers behavior from wired communication to wireless mobile communication makes companies competitive to providing the best services and products to make company revenue increased. In Telkomsel, the Average Revenue Per User (ARPU) generated from Kartu Halo as a postpaid card product that contributed 3.68 times more than the ARPU Telkomsel prepaid product at the end of 2017. There are various methods by the company to increased revenue growth, one of them were increasing market share. To increase the market share can be increase the customer base with offering products according to the intended customer segment. The purpose of this studies were to find out how the segmentation of Kartu Halo customers in Branch Manado based on lifestyle activities, interests, and opinions from consumers. This research is classified as a type of explorative descriptive research whose data collection is carried out by distributing questionnaires to 420 samples through social media of Kartu Halo product users at Branch Manado. The results of the questionnaire obtained valid and reliable results with a Chronbach's alpha value of 0.907. By using the two steps cluster of cluster analysis, the results of this study indicate that there are two clusters, namely the first cluster Experientials, which have Education and average income doing research, in choosing products, and running activities online. And the second cluster is Functionalist, who spends money on something important and has a high level of confidence.